Visualization of plaque distribution in a curved artery: three-dimensional intravascular ultrasound imaging. (31st October 2017) - Choi, Ahnryul; McPherson, David D.; Kim, Hyunggun
Abstract: Intravascular ultrasound (IVUS) imaging provides an excellent tool for evaluation of the type, morphology, extent, and severity of an atheromatous plaque. 3 D IVUS imaging offers additive information pertaining to morphology of the arterial structures and volumetric plaque distributions. A new 3 D IVUS visualization technique was developed to provide 3 D structural information of a curved artery. A virtual 3 D curved arterial phantom consisting of varying cross-sectional shapes, wall thicknesses, and acoustic intensity information was utilized to validate the nonlinear interpolation technique to create intermediary 2 D IVUS images. IVUS imaging was performed for the iliofemoral arterial segment of an atherosclerotic Yucatan miniswine model. These in-vivo IVUS data were utilized for intermediary IVUS image generation and volumetric 3 D IVUS visualization. Smooth transitional changes of cross-sectional shape, wall thickness and grayscale intensity were found between the intermediary images and the original arterial phantom slices. The 3 D IVUS imaging of the unfolded curved iliofemoral artery provided realistic 3 D luminal surface images of the arteries with physiologic grayscale intensity information. This unique 3 D IVUS imaging technique may help with assessment of 3 D plaque distribution across the curved arterial structure, and improve 3 D visualization of atheromatous components.